2016
DOI: 10.3892/ijmm.2016.2584
|View full text |Cite|
|
Sign up to set email alerts
|

Synergistic cardioprotective effects of Danshensu and hydroxysafflor yellow A against myocardial ischemia-reperfusion injury are mediated through the Akt/Nrf2/HO-1 pathway

Abstract: In clinical practice, the traditional Chinese medicinal herbs, Radix Salvia Miltiorrhiza and Carthamus tinctorius L., are usually prescribed in combination due to their significant cardioprotective effects. However, the mechanisms responsible for these combined effects remain unknown. Thus, in this study, we investigated the mechanisms responsible for the combined effects of Danshensu (DSS) and hydroxysafflor yellow A (HSYA) by establishing a rat model of myocardial ischemia/reperfusion (MI/R), as well as a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 47 publications
2
70
0
Order By: Relevance
“…Apoptotic index (AI) referred to the apoptotic degree. AI = apoptotic positive cell number/total cell number × 100% (Hu et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Apoptotic index (AI) referred to the apoptotic degree. AI = apoptotic positive cell number/total cell number × 100% (Hu et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…In another part, Hu et al. (2016) found that Danshensu, a main bioactive of Salvia miltiorrhizae , mainly exerted antiapoptotic effects acting on apoptosis‐related proteins, while hydroxysafflor yellow A, the main bioactive of safflower, had more significant effects on antioxidant enzymes. They concluded that the two bioactives acted in a complementary manner that manifested in synergistic antioxidant activity and protective effect against the myocardial ischemia‐reperfusion injury (Hu et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…(2016) found that Danshensu, a main bioactive of Salvia miltiorrhizae , mainly exerted antiapoptotic effects acting on apoptosis‐related proteins, while hydroxysafflor yellow A, the main bioactive of safflower, had more significant effects on antioxidant enzymes. They concluded that the two bioactives acted in a complementary manner that manifested in synergistic antioxidant activity and protective effect against the myocardial ischemia‐reperfusion injury (Hu et al., 2016). Similarly, in the present study, when petunidin and lycopene were mixed at the proper ratio, the synergistic effect was observed, which may be caused by concerted and complementary actions of the two individual compounds, that is, petunidin impacted more on the induction of NQO1 and lycopene on HO‐1, on top of the fact that both compounds upregulated the two enzymes individually.…”
Section: Resultsmentioning
confidence: 99%
“…It has been evidenced [30,31] that HSYA could be protected against kidney injury by its anti-inflammatory action. As an inflammatory mediator, TNF-α has a high correction with the extensive tubular damage in kidney [32,33]; as the previous study suggested, HSYA could inhibit the expression of tumor necrosis factor alpha (TNF-α) [34].…”
Section: Discussionmentioning
confidence: 99%